A Qualitative Study on the Barriers for Social Workers in Flanders (Belgium) to Provide Palliative Care and How to Overcome Them at the Micro, Meso and Macro Level. - Taels, Brent; Hermans, Kirsten; Audenhove, Chantal Van; Cohen, Joachim; Hermans, Koen; Declercq, Anja (British Journal of Social Work, 2024)
This qualitative study examines the barriers for social workers to perform tasks in Flemish palliative care and recommendations to overcome them in practice. It consists of two phases: a focus group phase with social workers from Flemish nursing homes, hospitals, health insurance and home care services and an expert panel phase with representatives from relevant care services and civil society organisations in Flanders. Data were analysed according to the Framework Method. Twenty-four social workers and twelve experts participated in this study. Three main barriers were identified along with two or three types of recommendations to overcome them in practice. A three-level strategy can be proposed to improve social workers' ability to perform tasks in palliative care. First, at a micro level, social workers' competencies for palliative care practice should be further increased. Second, at a meso level, the social work role in palliative care should be clarified by social workers themselves or by employers. Third, at a macro level, overarching care practices and policies facilitating the timely and structural integration of social workers should be implemented. Furthermore, this strategy will require the involvement of multiple actors, that is, social workers, education managers, care managers and policy makers.